Are "Climate Deniers" Rational Actors? Applying Weberian Rationalities to Advance Climate Policymaking. Issue 8 (17th November 2021) - Tangney, Peter
ABSTRACT: In recent decades, the label of Climate Denier has become an increasingly popular ad hominem device for climate change communications. Yet, what constitutes climate denial has evolved considerably from its original ascription for those who deny the physical science of anthropogenic global warming. This paper unpacks the multiple contemporary meanings of climate denial to examine whether this moniker can correlate with rational action (i.e. principled action logically derived from reliable knowledge), and how rationality can be deployed when pursuing political priorities that conflict with the orthodox normative positions of experts. Valid modes of rationality are diverse and not the sole preserve of those proponents of transformative and/or unified climate change action. Modes of rationality are also intimately linked to problem framing. Experts' existing problem-frames may actually facilitate Deniers' avoidance of the sorts of rationalisations that experts wish them to make. By better understanding the rationalities pertaining to the climate change debate, the paper concludes, experts and advocates can tailor their communication to more effectively influence the design of effective policies. A better understanding of how Climate Deniers can be rational and how rationalisation relates to problem framing may be necessary to address the most polarised politics of the climate crisis.